Marginal allografts in liver transplantation have a limited impact on length of stay. Issue 3 (13th December 2021) - Goff, Cameron; Zhang, Theodore; McDonald, Malcolm; Anand, Adrish; Galvan, Nhu Thao Nguyen; Kanwal, Fasiha; Cholankeril, George; Hernaez, Ruben; Goss, John A.; Rana, Abbas
Abstract: The study of marginal liver transplant outcomes, including post‐transplant length of stay (LOS), is necessary for determining the practicality of their use. 50 155 patients who received transplants from 2012 to 2020 were retrospectively analyzed with data from the Scientific Registry of Transplant Recipients database using Kaplan‐Meier survival curves and multivariable Cox regression. Six different definitions were used to classify an allograft as being marginal: 90 th percentile Donor Risk Index (DRI) allografts, donation after cardiac death (DCD) donors, national share donors, donors over 70, donors with > 30% macrovesicular steatosis, or 90 th percentile Discard Risk Index donors. 24% ( n = 12 124) of subjects received marginal allografts. Average LOS was 15.6 days among those who received standard allografts. Among those who received marginal allografts, LOS was found to be highest in those who received 90 th percentile DRI allografts at 15.6 days, and lowest in those who received DCD allografts at 12.7 days. Apart from fatty livers (95% CI .86–.98), marginal allografts were not associated with a prolonged LOS. We conclude that accounting for experience and recipient matching, transplant centers may be more aggressive in their use of extended criteria donors with limited fear of increasing LOS and its associated costs.